2016
DOI: 10.1084/jem.20151065
|View full text |Cite
|
Sign up to set email alerts
|

NKT sublineage specification and survival requires the ubiquitin-modifying enzyme TNFAIP3/A20

Abstract: Drennan et al. use a new mouse to show that A20-deficient NKT cells are hyperresponsive to TCR-dependent stimuli and have severely impaired NKT cell development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
(48 reference statements)
2
29
1
Order By: Relevance
“…demonstrated that splenic CD8 + T cells of naïve mice express A20 in vivo 32. In accordance with Giordano et al 31,.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…demonstrated that splenic CD8 + T cells of naïve mice express A20 in vivo 32. In accordance with Giordano et al 31,.…”
Section: Discussionsupporting
confidence: 83%
“…Of note, the increased activation of T cells, which has also been detected by Giordano et al 31,. did not result in a spontaneous inflammatory disease of CD4-Cre A20 fl/fl mice (our unpublished data), which has also not been described before3132. This may be explained by the fact that cytokine production of CD4 + (IFN-γ, IL-2) and CD8 + T cells (IFN-γ, granzyme B) was not increased in naïve CD4-Cre as compared to A20 fl/fl mice.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Unrestricted necroptosis in A20 −/− CD4 + cells led to reduced inflammation in a Th17‐cell‐dependent model of autoimmune encephalomyelitis . In NKT1 and NKT2 natural killer T (NKT) cell sublineages, A20 was also shown to restrict TCR‐dependent activation and survival, thereby controlling NKT cell differentiation . Prompted by the apparent contrast between anti‐inflammatory effects in various tissues and cell types on one hand and promotion of T helper cell survival on the other, we tested the functionality of A20 deficient CD4 + T cells in a mouse model of T cell‐dependent acute GVHD.…”
Section: Introductionmentioning
confidence: 99%